Social reference points and real-effort provision - Patrick Maus; María Montero; Martin Sefton (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2023)
We report a laboratory experiment testing whether social reference points impact effort provision. Subjects are randomly assigned the role of worker or peer and the worker observes the peer's earnings before participating in a real-effort task. Between treatments, we exogenously manipulate peer earnings. We find that the workers recall the earnings of their peer and are less satisfied with their own earnings when their peer earns more. Despite this, we do not observe a treatment effect in effort choices. Thus, although our subjects appear to care about income differentials, this does not translate to a change in behavior in our incentivized environment. We relate our results to recent studies of inequality and effort provision.
Keywords: D01; D31; D91; J31; 330; social comparisons; reference-dependent preferences; real-effortprovision; inequity aversion; relative income concerns